Perceived Closeness and Autistic Traits Modulate Interpersonal Vocal Communication - Sumathi, T. A.; Spinola, Olivia; Singh, Nandini Chatterjee; Chakrabarti, Bhismadev (Frontiers in Psychiatry, 2020)
Vocal modulation is a critical component of interpersonal communication. It not only serves as a dynamic and flexible tool for self-expression and linguistic information but also plays a key role in social behaviour. Variation in vocal modulation can be driven by individual traits of interlocutors as well as factors relating to the dyad, such as the perceived closeness between interlocutors. In this study we examine both of these sources of variation. At an individual level, we examine the impact of autistic traits, since lack of appropriate vocal modulation has often been associated with Autism Spectrum Disorders. At a dyadic level, we examine the role of perceived closeness between interlocutors on vocal modulation. The study was conducted in three separate samples from India, Italy, and the UK. Articulatory features were extracted from recorded conversations between a total of 85 same-sex pairs of participants, and the articulation space calculated. A larger articulation space corresponds to greater number of spectro-temporal modulations (articulatory variations) sampled by the speaker. Articulation space was associated positively with interpersonal closeness and negatively with autistic traits. This study thus provides novel insights into individual and dyadic variation that can influence interpersonal vocal communication.